Regional Healthcare Effectiveness - Kudelina, Olga Vladimirovna; Eremina, Sofya Leonidovna (Economy of Regions, 2016)
An evaluation of healthcare systems effectiveness of the regions of the Russian Federation (federal districts) was conducted using the Minmax method based on the data available at the United Interdepartmental Statistical Information System. Four groups of components (i.e. availability of resources; use of resources; access to resources and medical effectiveness) decomposed into 17 items were analyzed. The resource availability was measured by four indicators, including the provision of doctors, nurses, hospital beds; agencies providing health care to the population. Use of resources was measured by seven indicators: the average hospital stay, days; the average bed occupancy, days; the number of operations per 1 physician surgical; the cost per unit volume of medical care: in outpatient clinics, day hospitals, inpatient and emergency care. Access to the resources was measured by three indicators: the satisfaction of the population by medical care; the capacity of outpatient clinics; the average number of visits to health facility. The medical effectiveness was also measured by three indicators: incidence with the "first-ever diagnosis of malignancy"; life expectancy at birth, years; the number of days of temporary disability. The study of the dynamics of the components and indexes for 2008-2012 allows to indicate a multidirectional influence on the regional healthcare system. In some federal districts (e.g. North Caucasian), the effectiveness decreases due to resource availability, in others (South, North Caucasian) - due to the use of resources, in others (Far Eastern, Ural) - due to access to resources. It is found that the effectiveness of the healthcare systems of the federal districts differs significantly. In addition, the built matrix proves the variability the of effectiveness (comparison of expenditures and results) of healthcare systems of the federal districts of the Russian Federation: the high results can be obtained at high costs (the Far Eastern federal district) as well as at low costs (the Volga federal district). There is no possibility of reaching average results under any expenditures level (i.e. neither high, nor low, nor average). The proposed method of evaluation may become a basis for the creation of the strategic development programs of regional healthcare and the modeling of various scenarios for its realization while reaching the stable balance.